2015
DOI: 10.1371/journal.pone.0137912
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Body Mass Composition, Bone Mineral Density, Skin Fibrosis and 25(OH) Vitamin D Serum Levels in Systemic Sclerosis

Abstract: A reduced bone mineral density (BMD) is observed in several rheumatic autoimmune diseases, including Systemic Sclerosis (SSc); nevertheless, data concerning the possible determinants of bone loss in this disease are not fully investigated. The aim of this study is to evaluate the relationship between BMD, body mass composition, skin sclerosis and serum Vitamin D levels in two subsets of SSc patients. 64 post-menopausal SSc patients, classified as limited cutaneous (lcSSc) or diffuse cutaneous (dcSSc) SSc, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
(32 reference statements)
2
34
0
7
Order By: Relevance
“…Auto-antibodies profile, including anti-topoisomerase antibody I (Scl 70), anti-nuclear antibodies (ANA) and anti-centromere antibodies (ACA), has been reported to be associated with low hormone levels by Vacca et al, but following reports in the same findings failed [9][10][11]; [13][14][15][16][17]. Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Auto-antibodies profile, including anti-topoisomerase antibody I (Scl 70), anti-nuclear antibodies (ANA) and anti-centromere antibodies (ACA), has been reported to be associated with low hormone levels by Vacca et al, but following reports in the same findings failed [9][10][11]; [13][14][15][16][17]. Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the association with pulmonary and gastrointestinal tests have been greatly sought, but inconsistent data have been provided [9,11,13,14,16]; [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations